Introduction to Business Statistics - Weiers, Ronald M. (South-Western College Pub, 2012)
If you've ever felt intimidated or a little overwhelmed by business statistics, or if you simply want to master the power of these critical business skills, this book is for you. Weiers' INTRODUCTION TO BUSINESS STATISTICS, 6E speaks to you - today's student - introducing the fundamentals of business statistics in a conversational language and application setting that you can easily understand. Proven learning aids woven throughout the text, outstanding illustrations, and hundreds of examples build upon familiar, real-life experiences to help you develop a solid understanding of key statistical concepts. You'll discover how to use the statistical software most often chosen for business today. Also, you'll learn how to complete hand calculations and Excel applications - and when it's best to use each. To further your understanding of today's statistics, a powerful online learning system - CengageNOW - helps you maximize your study time and efficiently complete homework with tutorials and interactive learning tools designed to focus specifically on the areas you individually need to master for business statistics success. --This text refers to an out of print or unavailable edition of this title.